Teamwork as the key to mixing methods: lessons from multi-sited research designs. - Mazzucato, Valentina (Journal of Ethnic & Migration Studies, 2025)
Methodological literature often mentions the role of teamwork in mixed-methods research but rarely expounds upon it. I claim that much of the mixing in mixed-methods research occurs in the 'work' that teamwork entails. In multi-sited research designs, teamwork entails teams of researchers investigating different physical sites connected by the migration phenomenon under study. I draw on my experience leading five international, multi-year, multi-sited, mixed-methods, and team-based research projects in which teams investigated the simultaneous actions, emotions, and physical flows entailed in transnational relationships. The projects involved a combination of ethnographic studies and large-scale surveys. While tapping into my personal experiences to give detailed examples of the process of teamwork, I derive broader conclusions about the essential elements for teamwork that benefits the mixing of methods and multi-sited research. The paper discusses teamwork as a four-phase process in a research project and highlights praxes for sharing data within teams, adapting research strategies, and fine-tuning teamwork.